Difference of Children Ages 5-6 Years of Independence Viewed from The Caregiver (Parents and Grandparents) in Kindergarten Kartini 1 and Kartini 2 - Rahmawati, Enni; Diana, Diana (Jurusan PGPAUD FIP UNNES, 2016)
The child’s independence is characters that make a child in aged 0-6 years can stand by theirselves without depending in others, especially their parents. While many parents are working, parenting will in the hand of close relatives i.e. Grandma/Grandpa. This research aims to find out if there is a difference of child’s independence in terms of the subject matter of parenting (parents and grandparent). The population of this research are all students in kindergarten Kartini 1, and Kartini 2. The techniques that use in this research is purposive sampling technique. This research using a sample of children in the range of aged 5-6 years in class B that is parenting by parents and grandparent with a total number of 30 students. The Method analysis data collection is using child’s independence scale . Methods analysis data in this research using program SPSS16. This is demonstrated by the acquisition of the value t calculate < t table (0,268 < 2,048)and the value of sig. > 0.05 (0,791 > 0.05), then Ho denied. The conclusions of this research showed that there are differences between child’s independence that was parenting by their parents and grandparent.